Penerapan Motivasi Ekstrinsik dan Fleksibilitas Kerja Terhadap Kinerja Karyawan pada Divisi Marketing PT. Parastar Distrindo Sukabumi - Fauzhan Pratama Permana; Nor Norisanti; Resa Nurmala (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine whether the application of extrinsic motivation and work flexibility has an influence that can increase employee performance in the marketing field of PT. Parastar Distrindo Sukabumi Branch. This research method uses descriptive and associative research methods with a quantitative approach. The results of this study indicate that there is a positive and significant influence between extrinsic motivation on employee performance, and there is a positive and significant influence between work flexibility on employee performance and simultaneously the application of extrinsic motivation and work flexibility can improve the performance of marketing employees at PT. Parastar Distrindo Sukabumi Branch. In conclusion, there is a positive influence in the application of extrinsic motivation and work flexibility on the performance of employees in the marketing division. Keywords: Work Flexibility, Employee Performance, Extrinsic Motivation